Polygenic routes lead to parallel altitudinal adaptation in Heliosperma pusillum (Caryophyllaceae) - Aglaia Szukala; Jessica Lovegrove‐Walsh; Hirzi Luqman; Simone Fior; Thomas M. Wolfe; Božo Frajman; Peter Schönswetter; Ovidiu Paun (Molecular Ecology, 2023)
Understanding how organisms adapt to the environment is a major goal of modern biology. Parallel evolution—the independent evolution of similar phenotypes in different populations—provides a powerful framework to investigate the evolutionary potential of populations, the constraints of evolution, its repeatability and therefore its predictability. Here, we quantified the degree of gene expression and functional parallelism across replicated ecotype formation in Heliosperma pusillum (Caryophyllaceae), and gained insights into the architecture of adaptive traits. Population structure analyses and demographic modelling support a previously formulated hypothesis of parallel polytopic divergence of montane and alpine ecotypes. We detect a large proportion of differentially expressed genes (DEGs) underlying divergence within each replicate ecotype pair, with a strikingly low number of shared DEGs across pairs. Functional enrichment of DEGs reveals that the traits affected by significant expression divergence are largely consistent across ecotype pairs, in strong contrast to the nonshared genetic basis. The remarkable redundancy of differential gene expression indicates a polygenic architecture for the diverged adaptive traits. We conclude that polygenic traits appear key to opening multiple routes for adaptation, widening the adaptive potential of organisms.